154 Clinical indicators useful in decision-making about palliative chemotherapy for end-of-life ovarian cancer patients. (13th November 2020) - Hasegawa, K; Kiuchi, K; Kato, S; Motegi, E; Kosaka, N
Abstract : Introduction: Chemotherapy for end-of-life ovarian cancer patients is a complex and delicate problem. We evaluated whether active palliative chemotherapy is beneficial for such patients using inflammatory parameters, nutritional indicators, and the PPI (Palliative Prognostic Index), which predicts short-term prognosis. Methods: Thirty-six patients whose clinical data just before starting the last chemotherapy could be obtained among 49 patients who died from ovarian cancer from 2014 to 2019 were enrolled. Associations between the time from last chemotherapy to death and the following parameters were investigated: age, PS (performance status), NLR (neutrophil/lymphocyte ratio), PLR (platelet/lymphocyte ratio), mGPS (modified Glasgow prognostic score), PNI (prognostic nutritional index) score, and PPI score. Results: The median age was 57 (range, 19–80) years. The median time from last chemotherapy to death was 45.5 (range, 11–110) days. Eight patients (22%) died within 30 days of their last chemotherapy regimen. In univariate analysis, median survival time was significantly shorter in patients with higher NLR, mGPS 2, and higher PPI values; NLR (≥median vs. <median): 32 (range, 11–80) days vs. 54 (range, 35–110) days, p=0.008; mGPS (2 vs. 0–1): 42 (range, 11–80) days vs. 96 (range, 49–110) days, p=0.012; and PPI score (≥median vs. <median): 38 (range, 11–74) days vs. 60 (range, 18–110) days, p=0.005. However, in multivariate analysis, no factors were identified as independent prognostic factors for survival. Conclusion/Implication: Parameters such as NLR, mGPS, and PPI score may be indicators for discontinuation of palliative chemotherapy, and may be useful for maximizing end-of-life care for ovarian cancer patients.